If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 4 = -14 Reorder the terms: 4 + -2x = -14 Solving 4 + -2x = -14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -2x = -14 + -4 Combine like terms: 4 + -4 = 0 0 + -2x = -14 + -4 -2x = -14 + -4 Combine like terms: -14 + -4 = -18 -2x = -18 Divide each side by '-2'. x = 9 Simplifying x = 9
| (5x^2-7x+7)*(6x+9)=0 | | Y+5=4y-10 | | 7+2s-6=6s+8-3s | | 9x^2-34x-8=0 | | 13t-48=2+14t | | 5-2x=-5 | | 3z+15=27 | | 16x^2-320=88x | | 4x-8=12+3x | | 4x^2-2x-9=7x+8 | | 2(4x-3)-=4+2x | | 3z+17=27 | | 8a=3a+35 | | 6y-7=-2y+13 | | x(x+2)=168 | | 4x^2+47x+78=0 | | 15=b-5 | | 3+5n=16 | | -4+3x=-4 | | .3x=140+x | | .8333v+1.5=.875v+1.666 | | 2x^2+6x+9=225 | | (-4)=2x+5 | | 15=b-9 | | -6x-4=-10 | | 4(7x+8)+2=28x+34 | | 7x-2=2x+18 | | x+(x+1)+(x+2)=42 | | 5x+x+10=2*5x | | 3(3x-4)+2x=4x+16 | | 2x^2+102x+2601=5625 | | z+1.1z+2.4=-0.6(z+5) |